Web Based Library Information System At Public Senior High School 1 Tigapanah - Purba, Eviyanti Novita; Asnerlius Ginting, Aldi; Simamora, Roni J. (Ali Institute or Research and Publication, 2022)
Senior High School 1 Tigapanah is a high school located in Mulawari Village, Tigapanah District, Karo Regency. The existing system in the library is still done conventionally, namely by recording a list of members and transactions into a book. The data collection technique used is through survey methods and small interviews with respondents. The results obtained from this study indicate that the positive reinforcement with significant numbers in utilizing the school library comes from the invitation of friends, secondly from the teacher, from parents, from library facilities and finally from the librarian. While the negative reinforcement with significant numbers came from the teacher, the second was from discomfort factors such as stress and boredom, and the last was from the surrounding environmental conditions. In the library system, errors often occur in inputting so that data processing becomes slow and the calculation of fines given to students who are late in returning books to the library is often wrong. In paying attention to these problems, a system is needed that can process the existing transaction processes in the library. The programming languages ​​used are: PHP, HTML, CSS, and JavaScript. With this system, all activities make it easy for the library to process borrowing and returning transactions as well as calculating fines.